Terapi Bermain Meronce Untuk Mengembangkan Motorik Halus Pada Anak Berkebutuhan Khusus di Kelas Inklusi MI Al Ma’arif 02 Jombang Jember: Meronce Play Therapy to Develop Fine Motor in Children with Special Needs in Inclusion Class MI Al Ma'arif 02 Jombang Jember - Anisa Prafitralia; Imam Turmudi; Kharisma Intan Zahro (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Children with special needs are children with characteristics that are not the same as other normal children because they experience physical, mental, social and emotional limitations that affect their growth and development process. One of the disorders that occur in children with special needs is the difficulty in developing their fine motor skills. Children with special needs who have insufficient fine motor skills will be given a therapy related to fine motor development, one of which is by doing meronce play therapy. The focus of research in this thesis includes: 1. Can playing meronce therapy develop fine motor skills in children with special needs (ABK) in the inclusion class of MI Al Ma'arif 02 Jombang Jember?. 2. What are the factors that influence the development of meronce therapy for children with special needs in the inclusion class of MI Al Ma'arif 02 Jombang Jember?. The approach to this research is a qualitative approach with a descriptive research type. Data collection techniques using observation techniques, interviews and documentation. The data analysis technique uses data collection, data reduction, and data presentation. As for the validity of the data using source and technique triangulation. This study concluded that 1. Meronce play therapy can develop fine motor skills in children with special needs. The results showed that fine motor skills in children with special needs developed after being given meronce play therapy. 2. Factors that influence the development of fine motor skills come from a harmonious relationship between teachers and students, parenting styles, and the stimulus or stimuli given.